Identifikasi Muatan Al-Qur'an tentang Perintah Pendidikan Agama Islam Bagi Generasi Muda Umat Islam - Elsa Yulianingsih; Muhammad Tahajjudi Ghifary; Ahmad Ahmad; Siti Fatimah; Achmad Harristhana Mauldfi Sastraatmadja (Al-Ulum, 2022)
The focus of this article reveals the importance of early childhood education in an Islamic perspective, where the purpose of this article is to prepare generations with character and character. This study uses a qualitative approach to the type of literature research. The data analysis in this study used a phenomenological approach, namely examining the data obtained on a phenomenal problem so as to obtain research results. The results of the study show that Islam provides many examples of evidence in the Koran that can be used as guidelines in educating early childhood; For example, Surat al-Luqman which tells at length and clearly how to educate young people to become pious and pious children according to current conditions.